Teacher Preparation Process in the United States of America - Ayşe Elitok Kesici; Barış Çavuş (Athens Institute for Education and Research, 2022)
The purpose of this research was to reveal in-class communication practices used in the courses in the teacher preparation programs of the USA depending on classroom observations. Qualitative research method was used in the research. The researcher collected the data through direct participatory and unstructured observation. The researcher made observations in three different classes during the spring semester of 2017-2018 academic year. The study group of the observations was composed of three faculty members and the teacher candidates who were their students. According to research findings, positive faculty member behaviors were; not standing at the same point in the classroom, making eye contact with the students, etc., whereas negative faculty member behaviors were; speaking fast, not calling the students with their names, etc. Positive teacher candidate behaviors were; asking permission to speak by raising up a finger, taking notes in the lesson, etc., whereas negative teacher candidate behaviors were; texting friends during the lesson, sleeping in the lesson, coming to class late, etc. In order to train qualified teachers and make the outcomes of the lessons acquired by teacher candidates, the faculty members should enhance their teaching competencies in accordance with the changing conditions.